Incentive Conflicts, Bundling Claims, and the Interaction Among Financial Claimants. - Spatt, Chester S; Sterbenz, Frederic P (Journal of Finance, 1993)
The authors show that for certain capital structures equity has an incentive to buy out another claim and alter the firm's investment strategy so as to maximize the combined value of equity and the acquired claim. This restructuring may reintroduce agency problems into capital structures which appear to avoid agency conflicts. By bundling claims, it is possible to avoid this agency problem. The agency problem is also eliminated.by dispersed ownership of the claims.